Immunoexpression of interleukin-6 in drug-induced gingival overgrowth patients - P R Ganesh (Wolters Kluwer Medknow Publications, 2016)
Background: To analyze the role of proinflammatory cytokines in drug-induced gingival enlargement in Indian population. Aim: To evaluate for the presence of interleukin-6 (IL-6) in drug-induced gingival enlargement and to compare it with healthy control in the absence of enlargement. Materials and Methods: Thirty-five patients selected for the study and divided into control group (10) and study group (25) consisting of phenytoin (10); cyclosporin (10) and nifedipine (5) induced gingival enlargement. Gingival overgrowth index of Seymour was used to assess overgrowth and allot groups. Under LA, incisional biopsy done, tissue sample fixed in 10% formalin and immunohistochemically evaluated for the presence of IL-6 using LAB-SA method, Labeled- Streptavidin-Biotin Method (LAB-SA kit from Zymed- 2nd generation LAB-SA detection system, Zymed Laboratories, CA). The results of immunohistochemistry were statistically analyzed using Kruskaal-Wallis and Mann-Whitney test. Results: The data obtained from immunohistochemistry assessment shows that drug-induced gingival overgrowth (DIGO) samples express more IL-6 than control group and cyclosporin expresses more IL-6 followed by phenytoin and nifedipine. Conclusion: Increased IL-6 expression was noticed in all three DIGO groups in comparison with control group. Among the study group, cyclosporin expressed maximum IL-6 expression followed by phenytoin and nifedipine.